Kolaborasi Lintas Komunitas dalam Penyaluran Logistik Ramadan bagi Penyintas Bencana - Lilis Marlina; Luthfi Luthfi (Universitas Negeri Gorontalo, 2026)
This community service activity aimed to implement cross-community collaboration in distributing Ramadan food packages and cash assistance to survivors of flash floods and landslides living in emergency tents in Beutong Ateuh Banggalang, Nagan Raya, Aceh. Conducted on 15 February 2026, the activity involved Islam Selamatkan Negeri, student organizations of Universitas Teuku Umar, a campus Islamic organization, Akademi Komunitas Negeri Aceh Barat, and several Muslimah communities. A descriptive-participatory approach was applied through field observation, activity documentation, coordination with village officials, and direct aid distribution. Food packages and cash assistance were distributed in a coordinated manner despite crowding, unstable electricity, limited access to clean water, and light rain. The activity showed that collaboration among students, volunteers, religious communities, educational institutions, and village officials can support community-based humanitarian assistance. It also contributed to meeting part of the survivors’ basic needs before Ramadan and emphasized the importance of continuous post-disaster support.